Teacher Classroom Management Practices in an Inclusive Virtual Setting - M. Cortes, Venus; Montero, Arjie I.; Iligan, Mylene B.; Santillan, Donnameir Y.; B. Undalok, Stephanie (International Journal of Humanities and Education Development (IJHED), 2022)
The main purpose of this study is to explore the special education teacher’s classroom management strategies engagement in an inclusive virtual setting among the selected teachers in Region VII and one City in Region VIII during remote learning. Five respondents from two regions of Visayas were chosen using convenience and purposive sampling techniques. The researchers of this study used Descriptive Qualitative research design following Colaizzi’s method in thematic analysis. An online interview questionnaire was distributed to the respondents through Google forms and thematic analysis was used to analyze the data. The results indicated that teacher classroom management strategies undeniably played a vital role to maximize students’ engagement in an inclusive virtual classroom. On this basis, it is recommended that teacher classroom management practices should also investigate the variables that limit students' willingness to participate, as well as the importance of the entire class population in students’ engagement. And since our study solely identifies best practices and strategies to maximize student engagement, further study is needed to emphasize assessing teachers’ ICT skills, the parental factors, and appropriate assessment methods to give a greater understanding of the nature of why student engagement is declining in this new mode of learning.